2000
DOI: 10.1046/j.1525-1497.2000.06279.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of fibromyalgia with antidepressants

Abstract: Antidepressants are efficacious in treating many of the symptoms of fibromyalgia. Patients were more than 4 times as likely to report overall improvement, and reported moderate reductions in individual symptoms, particularly pain. Whether this effect is independent of depression needs further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
117
0
16

Year Published

2003
2003
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 304 publications
(136 citation statements)
references
References 47 publications
3
117
0
16
Order By: Relevance
“…Cardinal symptoms of FM are widespread body pain and a minimum of 11 out of 18 tender points evident for at least 3 months (1). One stream of research has focused on single modality treatments for FM such as medications (2,3) or exercise (4 -6). Although pessimism prevails with regard to prognosis (7,8), a consensus has emerged that exercise is one critical component of treatment for patients with FM (9).…”
Section: Introductionmentioning
confidence: 99%
“…Cardinal symptoms of FM are widespread body pain and a minimum of 11 out of 18 tender points evident for at least 3 months (1). One stream of research has focused on single modality treatments for FM such as medications (2,3) or exercise (4 -6). Although pessimism prevails with regard to prognosis (7,8), a consensus has emerged that exercise is one critical component of treatment for patients with FM (9).…”
Section: Introductionmentioning
confidence: 99%
“…Antidepressants have an antinociceptive effect on various forms of pain but none of the antidepressant drugs, have yet been approved by the FDA for the treatment of FM (10)(11)(12)(13)(14). The recent meta-analyses of antidepressant trials have shown that tricyclic antidepressants to be moderately effective in the treatment of patients with FM (7,15). Although the studies evaluating the effects of selective serotonin reuptake inhibitors (SSRIs) in the treatment of FM yielded inconsistent results, these medications are better tolerated than the tricyclic antidepressants (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis, O'Malley et al (12) found that benefits were mild for fatigue and moderate for sleep, overall well-being, and pain severity. The measure least likely to improve was tenderness.…”
Section: Modulation Of Monoamines In Fmsmentioning
confidence: 99%